The Other(s) Principle(s): A Screenplay Exploring Childfree Issue in Indonesia - Olivia Agatha (Institute of Research and Community Outreach - Petra Christian University, 2022)
Childfree has become one of few topics still considered taboo in Indonesia. This creative work aims at helping Indonesian childfree women fight for their voices to be heard. Secondary research is used as a methodology to complete the thesis. The data are gathered from journals, e-books, credible website, and online articles. To support the findings, theories that are used are gender role and attachment theory. This thesis explores the reason women decide to be childfree is the toxic relationship in the family. The thesis is in the form of a screenplay using drama-romance genre. It tells a story about Ebba who struggles to be accepted by her family and friends. She had a rough relationship with her mother from her childhood phase until now. Her boyfriend, Bisma, distances himself after finding out that Ebba is a childfree woman However, they manage to reconcile and Ebba gets married to Bisma.